Growing hulled wheat and old bread wheat genotypes in non-marginal environments: agronomic, qualitative, and safety insights - Sardella, Claudia; Vanara, Francesca; Scapino, Mattia; Scarpino, Valentina; Pedrazzani, Clara; Dall’Asta, Chiara; Blandino, Massimo (Frontiers in Plant Science, 2025)
Hulled wheats (einkorn, emmer, and spelt) and old genotypes of bread wheat (T. aestivum L. ssp. aestivum) have been attracting attention in plant breeding and in the food industry for food diversification and value addition purposes. This study investigated the agronomic behavior, the grain quality, the contaminants, the bioactive compounds (e.g., alkylresorcinols and phenolic acids), and the antioxidant capacity (FRAP and DPPH) of modern genotypes of hulled wheat (einkorn, emmer, and spelt), as well as old Italian bread wheat genotypes, under standard cropping conditions. These genotypes were compared with modern bread wheat genotypes used as commercial references in four location-by-year experiments in Northwest Italy. The treatments were assigned to experimental units using a completely randomized block design and three replications. The modern bread wheat genotypes displayed better agronomic performance, while the old bread wheat genotypes had higher protein contents, but were characterized by higher dough weakening, even with increasing levels of nitrogen fertilization. The old genotypes did not offer advantages in terms of toxic celiac disease epitopes, but exhibited an overall reduced susceptibility to mycotoxin accumulation, although a large variability was observed within the modern hulled and bread wheat genotypes. The bioactive compound content and the antioxidant capacity were closely related to the growing conditions. Majority of the differences among the genotypes emerged from the soluble fraction of phenolic acids, with a slightly higher content in the old bread wheat genotypes than in the modern ones and a different profile for the hulled wheats. On the other hand, the alkylresorcinol content was higher in the modern genotypes than in the old ones and was closely related to kernel size. Overall, the results highlighted considerable differences among genotypes and a broader variability in the modern genotypes than the old ones for many of the studied traits. Substantial agronomic and qualitative differences were observed within the hulled wheats, thus suggesting opportunities for genetic selection and the development of improved hulled or bread wheat genotypes.